Effect of sprint approach velocity and distance on deceleration performance in NCAA Division I female softball players - Philipp, N. M.; Blackburn, S. D.; Cabarkapa, D.; Fry, A. C. (Journal of Human Sport & Exercise, 2023)
Team sports require athletes to rapidly reduce whole body momentum and velocity, to efficiently change direction, or to avoid defenders. Decelerations often occur following varying approach distances and velocities. The aim of this study was to investigate the effects of different sprinting approach distances, and therefore velocities and momenta on measures of horizontal deceleration performance within female NCAA Division I softball players. Athletes performed an acceleration:deceleration assessment (ADA) over 20 yards (18.29 m) (ADA20) and 10 yards (9.14 m) (ADA10), respectively. The sample was divided into high and low performance groups for approach velocity and approach momentum, and between-group differences were studied for each test. Correlations between measures of deceleration were analyzed between the ADA10 and ADA20. Results suggested that during the ADA20 trials, athletes initiated the deceleration phase at greater approach velocities (p < 0.001, ES = 2.71) and momenta (p < 0.001, ES = 2.65), generating greater reductions in velocity (p < 0.001, ES = 1.60) and momentum (p < 0.001, ES = 1.50). Within the ADA10, athletes within the high velocity group saw significantly greater reductions in velocity (p = 0.009, ES = 1.24). This was not observed within the ADA20. A significant negative association was found between average deceleration within the ADA10 and ADA20 (r = -0.443, p = 0.039). Findings suggest that horizontal decelerations are influenced by the approach distance, velocity, and momentum, which athletes are exposed to before initiating the deceleration phase. This should be accounted for when implementing training to enhance such qualities.